Food Security of the Inhabitants of the Cucaita Village (Briceño, Boyacá) Period 2018-2022: A Reflective View (2023)
The program “FINCA Fund, We Believe in the Countryside” is an initiative that seeks to promote agriculture and food security in rural communities in Colombia. In order to analyze the food security of the inhabitants of the village of Cucaita of Briceño, Boyacá, in this work, a methodology with a mixed approach was used to document the policies on food security and survey 73 beneficiary families of the program. A sociodemographic characterization and the productive evaluation and estimation of food security through the standardized Lorenzana questionnaire were carried out. National and departmental programs were found to be varied in supporting the quality of life of rural inhabitants, but with greater experience in the school feeding program (PAE, by its acronym in Spanish). The prevalence of the low category was demonstrated ¾in terms of income, educational level, ownership and size of the real estate¾, and the predominance of “pancoger” crops (crops that satisfy part of the nutritional needs of a given population) and the use of inputs from the program, that favored the self-consumption of products, leveraging food security, that was not found to be reduced.